"Je suis … Charlie, Samuel, Muhammed": Practicing Muhammed Cartoons in Far Right and Islamist Politics. Issue 4 (December 2022) - de Groot Heupner, Susan
Abstract: Since the 2005 Jyllands-Posten controversy, both far right and Islamist actors have employed Muhammed cartoons to construct a radical frontier between Muslims and non-Muslims. This article aims to provide a better understanding of the linkages between two opposing forms of popular identification by looking at the utilization of the Muhammed cartoons to crystallize a multitude of (conflicting) subjects, affects, and demands. Following a vantage point of mutual relations, the article investigates the discursive performances of the Dutch branch of the transnational Islamist party Hizb ut-Tahrir and the far right Party for Freedom with respect to the Jyllands-Posten affair, the 2015 Charlie Hebdo attacks, and the 2020 killing of a French schoolteacher. Considering its cultural and political foundations of mutual respect and tolerance, the Dutch case is pertinent for examining the tension between the right to free speech and support for extremist and popular forms of (far right and Islamist) identification.